T Cell Phenotype in Allergic Asthma and Atopic Dermatitis - Wohlfahrt, Jan G.; Kunzmann, Steffen; Menz, Günther; Kneist, Werner; Akdis, Cezmi A.; Blaser, Kurt; Schmidt-Weber, Carsten B. (International archives of allergy and immunology, 2003)
Background: T cells are key regulators of immunologic disease parameters. However, their contribution to the process of tissue remodeling is ill defined. In the present study, we investigated gene expression of allergy-characteristic, IL-4-rich T cell cDNAs to monitor expression of genes that might participate in the pathogenesis of allergic diseases. Methods: cDNAs of freshly isolated and restimulated CD4+ T cells from patients with allergic asthma (AA) or atopic dermatitis (AD) and healthy subjects were analyzed on Nylon membrane-based DNA arrays. Three patients were selected for an allergy-characteristic T cell phenotype with high IL-4 expression (AA) or IL-13 expression (AD). Results: Several gene families such as the TGF-β family, chemokines and chemokine receptors were found to be upregulated. Matrix metalloproteinases and their inhibitors were also found to be expressed in an enhanced manner. Furthermore, factors regulating tissue turnover such as fibroblast growth factors and neurotrophic as well as vasoactive factors were found be expressed at a higher level in allergic patient compared to healthy donors. Conclusion: The present study reveals and confirms genes relevant for allergy and highlights an approach to applying a DNA array technique for diagnostic discrimination of allergic diseases.